2019
DOI: 10.3390/jcm8071084
|View full text |Cite
|
Sign up to set email alerts
|

Silent Myocardial Perfusion Abnormalities Detected by Stress Cardiovascular Magnetic Resonance in Antiphospholipid Syndrome: A Case-Control Study

Abstract: Objective: To examine the prevalence of silent myocardial ischemia and fibrosis in antiphospholipid syndrome (APS), using stress cardiovascular magnetic resonance (CMR). Methods: Forty-four consecutive APS patients without prior cardiac disease (22 primary APS, 22 systemic lupus erythematosus (SLE)/APS, mean age 44 (12.9) years, 64% women) and 44 age/gender-matched controls were evaluated using CMR at 1.5 T. Steady-state free precession imaging for function assessment and adenosine stress-CMR for perfusion-fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 41 publications
(50 reference statements)
1
9
1
Order By: Relevance
“…Lastly, another point that merits discussion is the significantly lower LV mass that was identified in patients with IJD when compared with controls in our study. Such findings have also been reported in the past by our group in patients with antiphospholipid syndrome and systemic sclerosis with concomitant cardiac involvement [ 19 , 32 ], as well as in patients with RA by other researchers [ 33 ]. However, other studies have not been able to reproduce this finding [ 12 ].…”
Section: Discussionsupporting
confidence: 88%
“…Lastly, another point that merits discussion is the significantly lower LV mass that was identified in patients with IJD when compared with controls in our study. Such findings have also been reported in the past by our group in patients with antiphospholipid syndrome and systemic sclerosis with concomitant cardiac involvement [ 19 , 32 ], as well as in patients with RA by other researchers [ 33 ]. However, other studies have not been able to reproduce this finding [ 12 ].…”
Section: Discussionsupporting
confidence: 88%
“…As such, this demonstrates the need for a combined brain and heart MRI examination in ARD patients with cardiac symptoms, seeing as disease progression may evolve differently in the two organs. Notably, our group has previously reported that CMR findings are independent of C-reactive protein levels in ARD patients [47,51,52], often rendering biomarker-based pre-selection of patients for CMR examinations problematic. This would explain the current findings and suggests that such inflammatory biomarkers might have greater utility in evaluating brain involvement than cardiac involvement, although this needs to be corroborated by future independent studies.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with chronic LV dysfunction due to CAD, delayed enhancement CMR was found to provide the highest sensitivity and negative predicting value for predicting improved segmental LV contractile function after revascularization, whereas low dose dobutamine CMR provides the best specificity and positive predicting value [ 29 ]. Stress CMR has been studied for the detection of silent ischemia in patients with antiphospholipid syndrome [ 30 ]. In another study which enrolled children with Kawasaki disease and CAD, stress CMR was found to have 100% positive agreement and >90% negative and overall agreement with moderate to severe coronary artery stenoses as depicted by coronary artery angiography [ 31 ].…”
Section: The Role Of Cmr In the Detection Of Significant Cadmentioning
confidence: 99%